Images of health among hospital patients in Jordan: A qualitative study - Shoqirat, Noordeen Awath (International Journal of Advanced Nursing Studies, 2012)
The purpose of this study was to examine hospital patients’ understanding of health and its cultural constructions in Jordan. Focus group discussions (n=4) were carried out with hospital patients. The findings showed three images of health among patients in Jordan with different complexity levels. This included health as the freedom from illness, health as being in good social and psychological wellbeing, health as being physically, psychologically, socially and economically satisfied. Gender related conceptualisation of health have been associated with the role of men and women in the society. Hospital patients’ understanding of health is diverse, multidimensional, and affected by their gender. Therefore, hospital nurses are urged to incorporate patients’ conceptualisations of health and factors involved into the framework of the patient’s daily care plan and health promotion activity. The study limitations and recommendations for practice and future research are also outlined. Keywords: focus group discussions, health, hospital patients, culture, Jordan, nursing